The Influence of the Personality Competence of Islamic Education Teachers on the Learning Motivation - Ajie Setiaji; Abdul Holik; Sani Gunari (Universitas Muhammadiyah Enrekang, 2022)
This research is motivated by the learning process of students who are less enthusiastic in learning, the objectives of this research are as follows: 1). To know the reality of PAI teacher's personality, 2). To know the reality of students' learning motivation and 3). To determine the effect of the independent variable (personality competence) of PAI teachers on the dependent variable (learning motivation) of students, this study used a quantitative approach and took the form of a survey. The sample used was class X students majoring in visual communication design at SMKN 14 Bandung with a total population of 101 students. Data collection techniques using the method of observation, questionnaires and documentation. The data analysis technique used classical assumption test, normality test, linearity test and heteroscedasticity test. Meanwhile, hypothesis testing uses simple regression analysis and is strengthened by the coefficient of determination. The results showed that 1). The Reality of the personality competence of Islamic education teachers on average (mean) for each indicator data obtained a mean value of > 4.00 or was in the interval of 4.00-5.00 which means very good. 2). The reality of student learning motivation on average (mean) data for each indicator is obtained a mean value of > 3.00 or is in the interval of 3.00-4.00 which means it is good. 3). The significance of the coefficients table is 0.008 < 0.05, which means that the independent variable has a significant effect on the dependent variable.